2013
DOI: 10.1016/j.immuni.2013.03.009
|View full text |Cite
|
Sign up to set email alerts
|

IRF4 Transcription-Factor-Dependent CD103+CD11b+ Dendritic Cells Drive Mucosal T Helper 17 Cell Differentiation

Abstract: CD103(+)CD11b(+) dendritic cells (DCs) represent the major migratory DC population within the small intestinal lamina propria (SI-LP), but their in vivo function remains unclear. Here we demonstrate that intestinal CD103(+)CD11b(+) DC survival was dependent on interferon regulatory factor 4 (IRF4). Mice with a DC deletion in Irf4 displayed reduced numbers of intestinal interleukin 17 (IL-17)-secreting helper T 17 (Th17) cells and failed to support Th17 cell differentiation in draining mesenteric lymph nodes (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

56
608
8
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 511 publications
(675 citation statements)
references
References 67 publications
56
608
8
3
Order By: Relevance
“…In addition, two recent reports showed that an IFN regulatory factor 4 (IRF4)-dependent, IL-6-producing CD11b + dendritic cell population was required for Th17 cell differentiation (27,28). Although it was not shown in these studies that the IRF4-dependent CD11b + dendritic cells expressed CD301b, it is possible as CD301b + dermal dendritic cells account for a large fraction of the CD11b high migratory dendritic cell population.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, two recent reports showed that an IFN regulatory factor 4 (IRF4)-dependent, IL-6-producing CD11b + dendritic cell population was required for Th17 cell differentiation (27,28). Although it was not shown in these studies that the IRF4-dependent CD11b + dendritic cells expressed CD301b, it is possible as CD301b + dermal dendritic cells account for a large fraction of the CD11b high migratory dendritic cell population.…”
Section: Discussionmentioning
confidence: 96%
“…The lamina propria (LP) contains a variety of DCs and macrophage subsets. One such subset expresses integrin αE (CD103) and has the ability to drive IL-17-producing T cells (5,6). The CX3C chemokine receptor 1 (CX 3 CR1) + cells that express integrin αX (CD11c) and a macrophage marker, F4/80 but not CD103 are crucial for the sampling of luminal antigens through their use of projecting dendrites that penetrate the epithelial cell layer (7)(8)(9).…”
mentioning
confidence: 99%
“…Ontogenetically, NLT CD11b + DCs (expressing MHC-II, CD11c and CD11b) were thought to arise from both bone marrow (BM) DC-specific progenitors and monocytes, with partial dependence on both FLT3 and the macrophage/monocyte lineage growth factor receptor, CSF-1R, for their differentiation [7]. However, reanalysis of the CD11b + DC compartment using CD24 (DC marker) and CD64/MerTK (macrophage markers) improved discrimination of DCs and macrophages, revealing the true bona fide DC nature of the CD24 + CD11b + population, which is purely dependent on FLT3 for its differentiation [8,9]. CD11b + DCs were also found to depend on various other transcription factors (TFs) such as NOTCH2, RELB and IRF4 [6,[8][9][10].…”
mentioning
confidence: 99%
“…However, reanalysis of the CD11b + DC compartment using CD24 (DC marker) and CD64/MerTK (macrophage markers) improved discrimination of DCs and macrophages, revealing the true bona fide DC nature of the CD24 + CD11b + population, which is purely dependent on FLT3 for its differentiation [8,9]. CD11b + DCs were also found to depend on various other transcription factors (TFs) such as NOTCH2, RELB and IRF4 [6,[8][9][10]. These recent developments illustrate the importance of analyses of growth factor and TF requirements of DC subsets in advancing our understanding of their inter-relationships.…”
mentioning
confidence: 99%
See 1 more Smart Citation